Ultrasmooth and Dense Lithium Deposition Toward High‐Performance Lithium‐Metal Batteries. Issue 15 (2nd March 2023) - Yang, Zhilin; Liu, Wei; Chen, Qian; Wang, Xingguo; Zhang, Weili; Zhang, Qiannan; Zuo, Jinghan; Yao, Yong; Gu, Xiaokang; Si, Kunpeng; Liu, Kai; Wang, Jinliang; et al.
Abstract: Lithium (Li)‐metal batteries (LMBs) with stable solid electrolyte interphase (SEI) and dendrite‐free formation have great potential in next‐generation energy storage devices. Here, vertically aligned 3D Cu2 S nanosheet arrays are fabricated on the surface of commercial Cu foils, which in situ generate ultrathin Cu nanosheet arrays to reduce local current density and Li2 S layers on the surfaces to work as an excellent artificial SEI. It is found that Li presents a 3D‐to‐planar deposition model, and Li2 S layers are reversibly movable between the 3D nanosheet surface and 2D planar surface of Li during long‐term cycling. This enables ultrasmooth and dense Li deposition at 1 mA cm ‐2, presenting an average thickness of ≈53.0 µm at 10 mAh cm ‐2, which is close to the theoretical Li foil thickness and is highly reversible at different cycles. Thus, 1150 stable cycles with high Coulombic efficiency (CE, 99.1%) at ether‐based electrolytes and 300 stable cycles with high CE (98.8%) at carbonate electrolytes are realized in half‐cell with a capacity of 1 mAh cm ‐2 at 1 mA cm ‐2 . When coupled with commercial cathodes (LiFePO4 or LiNi0.8 Co0.1 Mn0.1 O2 ), the full cells present substantially enhanced cyclability under high cathode loading, limited (or zero) Li excess, and lean electrolyte conditions, even at −20 °C. Abstract : Ultrasmooth and dense lithium  deposition is achieved by ingenious synergy of vertically aligned nanosheet arrays and ultrathin Li2 S‐rich solid electrolyte interphase (SEI). Specifically, nanosheet arrays possess the proper surface area to reduce local current density and avoid excessive side reactions. Moreover, moveable Li2 S‐rich SEI with electronically insulating properties can homogenize lithium‐ion flux and inhibit electron escape to avoid electrolyte decomposition.